2015
DOI: 10.1007/s00128-015-1714-2
|View full text |Cite
|
Sign up to set email alerts
|

4,4′-DDE and Endosulfan Levels in Agricultural Soils of the Çukurova Region, Mediterranean Turkey

Abstract: Mediterranean Turkey has long been at the forefront of Turkish agriculture and the use of organochlorinated pesticides (OCPs) in this area rose considerably between the 1940s and 1980s. This study aimed to determine OCP residue levels in agricultural soils collected from the Mersin and Adana Districts, Çukurova Basin in Mediterranean Turkey. Most soil samples were contaminated with one, or both, of two OCP metabolites; 4,4'-dichlorodiphenyldichloroethylene (4,4'-DDE) and endosulfan sulfate. 4,4'-DDE occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
3
1
Order By: Relevance
“…As shown in Table 5 and Figure 5 (summations), we found significant differences in the concentrations of p,p’-DDE, p,p-DDD, and dieldrin, although in the opposite directions to those theorized by other authors [ 72 , 73 ]. Our results indicated that the concentration of organochlorines in farms devoted to mixed vegetable cultivation was much higher than that in vineyards, which would present levels very much in line with those reported recently in studies around the world [ 65 , 66 , 67 , 68 , 69 ]. This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Table 5 and Figure 5 (summations), we found significant differences in the concentrations of p,p’-DDE, p,p-DDD, and dieldrin, although in the opposite directions to those theorized by other authors [ 72 , 73 ]. Our results indicated that the concentration of organochlorines in farms devoted to mixed vegetable cultivation was much higher than that in vineyards, which would present levels very much in line with those reported recently in studies around the world [ 65 , 66 , 67 , 68 , 69 ]. This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place.…”
Section: Resultssupporting
confidence: 91%
“…This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place. much in line with those reported recently in studies around the world [65][66][67][68][69]. This further highlights the need for robust and reliable analytical tools to routinely monitor levels of persistent and semi-persistent organic pollutants because, as we have seen, levels can vary greatly from place to place.…”
Section: Application To Agricultural Soil Samplessupporting
confidence: 87%
See 1 more Smart Citation
“…Excessive application and improper handling of pesticides affect the environment and cause serious health problems to human beings and animals. Organochlorine pesticides are persistent and bio-accumulate in the environment (Akca et al 2016 ; Fiedler et al 2013 ). They cause ecological problems and have a great impact on human health (Agarwal et al 2015 ; Fiedler et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fungicide cyazofamid has a short life in differently textured agricultural soils and therefore has little chance of contaminating groundwater [102]. OCs and their metabolites pose a grave risk in agricultural soils as OCs were detected in 27 of 29 soil samples tested in Turkey and ranged from 6 to 1090 μg kg −1 dry soil in areas where OCs were heavily used between the 1940s and 1980s in Turkey [2]. 4,4′-DDE was present above the acceptable risk levels in the agricultural soils of Mersin District in Turkey [2].…”
Section: Different Types Of Pesticides In the Environmentmentioning
confidence: 99%